Sistem Informasi Keamanan Berbasis Web Kamera Melalui SMS - Irfan Darmawan; Firmansyah Maulana S. N. (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
Basic of security system with camera is saving all event without stopping, that couse system need a bigcapasity of hard disk. Apart form that, system need a operator for monitoring, control and measure if somethinghappen. So, that can not do if in travel.Security system solution is system only save video on fixed times, monitoring and control can do fromlong distance and there is a report if something happen on territory in watch.Form result of security system act of planning, that only save video if something happen on territory inwatch. Monitoring and control to change position of camera with turn motor stepper that connected to computerparallel port can do from long distance use internet facilities. And a report of something happen send use a SMSfor immediately measure.So, conclusion is security system not need a big capasity of hard disk, becouse system only save smallcapasity of files. Video streaming can use for monitoring and camera position change use internet facility. Thetime that refort send use SMS facility for territory owner.Keywords: Camera Server, Server, Client, Internet, Parallel Port, Motor Stepper, Webcam, Ponsel, SMS, VideoStreaming.